Attitudes Toward Interprofessional Education: Comparing Physical Therapist and Other Health Care Professions' Students. Issue 2 (June 2018) - Smith, Barbara S.; Anderson, Kelly
Abstract : Background and Purpose: Interprofessional teams provide the potential of comprehensive and reliable care for patient/clients with complex problems. Interprofessional education (IPE) may change students' attitudes and knowledge necessary to maintain interprofessional (IP) teamwork after graduation. Learning experiences that include interaction with standardized patients enable students to increase their skills to become IP health care providers. This case study assessed the first-time experience of a College of Health Professions in using standardized patients for an IPE activity. Case Description: Interprofessional student teams, representing 178 students, were formed representing the following health professions education programs: physical therapist (PT), physician assistant (PA), communication sciences and disorders (CSD), dental hygiene (DH), nursing, medical laboratory science, and public health. Standardized patients interacted with the students. Students participated in a faculty facilitator–guided discussion related to each disciplines' professional roles and patient care goals. Each discipline had faculty representation. Students received feedback from standardized patients and faculty facilitators. A pre-post design was used with a mixed quantitative–qualitative methodology. Quantitative data were analyzed using 1-way analysis of variance. Qualitative data were evaluated using frequency data. Outcomes: Only PT, PA, CSD, and DH students participated in sufficient numbers for use in analyses. All groups improved their ratings on the postsurvey statements. Percentages of students whose ratings improved on the postevent survey were examined by department. Physical therapist and PA students showed similar percentages. These percentages of improvements were smaller than improvements of CSD and DH students. Qualitative analysis of open-ended questions revealed four themes: collaborating without judgment of others, learning about the roles and responsibilities of their profession, as well as those of other professions, learning about themselves, and communicating with different personalities. Discussion and Conclusion: Students' perceptions of themselves and of other health care professional students changed. Overall, this 4-hour IPE exercise had a positive influence on these students' attitudes toward working as a team member and in being an effective member of that team. Abstract : Supplemental Digital Content is Available in the Text.